Optimization of Wet Rendering and Alkali Neutralization for Omega-3-Rich Oil Production from Milkfish (Chanos chanos) - Ilham Ahmad; Rahmawati Saleh; Nurlaeli Fattah; Imran Muhtar; Luthfiah (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the instability, off-flavors, and variable quality that limit the use of fish oil as an omega-3 source, particularly from milkfish (Chanos chanos). The research aims to produce omega-3-rich milkfish oil that meets international quality standards and is suitable for microencapsulation. Fresh milkfish was processed using wet rendering at four temperatures (70, 80, 90, and 100°C) and three heating times (30, 40, and 60 min). The crude oil was then refined by alkali neutralization with different NaOH concentrations. Oil yield and oxidative quality parameters—peroxide value, p-anisidine value, total oxidation (TOTOX), and acid value—were measured and analyzed using factorial ANOVA. The highest yield (0.29%) was obtained at 100°C for 60 min. Peroxide and anisidine values (3.44 and 11.75 meq/kg) and TOTOX (<20 meq/kg) complied with International Fish Oil Standards, whereas acid values (2.43–2.68 mg KOH/g) exceeded the limit at prolonged high-temperature extraction. These results indicate that higher temperatures increase oil recovery but promote hydrolytic degradation. Careful optimization of time and temperature is therefore required to obtain stable, high-quality omega-3 milkfish oil for further microencapsulation and application in health-oriented food products.